Development of a new efficient and economical magnetic sorbent silicone surfactant-based activated carbon for the removal of chloro- and nitro-group phenolic compounds from contaminated water samples. Issue 63 (13th November 2019) - Gopal, K.; Mohd, N. I.; Raoov, M.; Suah, F. B. M.; Yahaya, N.; Zain, N. N. M.
Abstract : In this study, activated carbon (AC) coated with a green silicone surfactant (SS) was further incorporated with magnetite particles (Fe3 O4 ) to enhance the separation of the newly designed magnetic AC–SS (Fe3 O4 @AC–SS) in a magnetic field. Abstract : In this study, activated carbon (AC) coated with a green silicone surfactant (SS) was further incorporated with magnetite particles (Fe3 O4 ) via a co-precipitation method to enhance the separation of the newly designed magnetic AC–SS (Fe3 O4 @AC–SS) in a magnetic field. The properties of this magnetic adsorbent were characterized via Fourier transform-infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The adsorption characteristics of the Fe3 O4 @AC–SS adsorbent were examined using 2, 4-nitrophenol and 2, 4-dichlorophenol as adsorbates. Experiments were performed to investigate the adsorption kinetics, isotherms, thermodynamics as well as the effects of adsorption dosage and solution pH on the removal of both analytes. The kinetic data were well-fitted by the pseudo-second order model and the Freundlich model best described the adsorption isotherm for both analytes. The maximum adsorption capabilities for 2, 4-dinitrophenol and 2, 4-dichlorophenol reached 43 and 98 mg g −1, respectively. The analysis was further validated using real industrial effluent, and a removal efficiency of 62.2–98.1% and relative standard deviation value less than 7.2% were attained for both analytes. Thus, the multifunctional adsorbent has potential to function as an adsorbent for the fast, convenient, economical and highly efficient removal of pollutants from wastewater, which is significant for the purification of natural water and industrial effluent.